ANALISIS WACANA KRITIS PADA TEKS EDIOTORIAL DAN OPINI DENGAN MENGGUNAKAN TEORI NORMAN FAIRCLOUGH - Yugoyekti, Ahmad; Megawati, Megawati; Kuryanti, Tri; Sajuni, Ahmad (Jurnal Buana Kata: Pendidikan, Bahasa, dan Ilmu Komunikasi, 2024)
Language is a communication tool that is closely related to human daily life. Language is useful as a thinking tool as well as a means of connecting and determining the identity of an individual. There are various written works that use language as the media they ask for, one of which is editorial and opinion texts, editorial texts are texts that contain opinions based on certain views not personal views, while opinion texts are texts that contain thoughts, feelings, opinions and response to an issue. Furthermore, texts like this can be analyzed using critical discourse analysis. Critical discourse analysis is the use of language in speech and writing as a form of social oratic. Critical discourse analysis has various theories, one of which is critical discourse analysis with the Norman Fairclough model which is considered complete, which divides text into three dimensions, these dimensions include: (a) Textual dimension (Microstructural) which includes representation, relations and identity, (b) Dimension of text production practices (Meso-Structural) which includes text production, text distribution and text consumption, (c) dimension of socio-cultural practices (Macrostructural) which includes institutional, situational and social. From the results of the analysis carried out, these three dimensions were found in the news that was used as the object of study. Thus, the news is considered good and appropriate.   Bahasa merupakan alat komunikasi yang erat kaitannya dengan keseharian manusia. Bahasa bermanfaat sebagai alat berfikir serta alat penghubung dan penentu identitas seorang individu. Terdapat berbagai karya tulis yang menggunakan bahasa sebagai media penyampaiannya, salah satunya ialah teks editorial dan opini, teks editorial adalah teks yang didalamnya berisi opini yang didasarkan pada pandangan tertentu bukan pandangan pribadi, sedangkan teks opini merupakan teks yang berisi pikiran, perasaan, pendapat maupun tanggapan mengenai suatu isu. Selanjutnya teks seperti ini dapat dianalisis dengan menggunakan analisis wacana kritis. Analisis wacana kritis adalah adalah penggunaan bahasa dalam tuturan dan tulisan sebagai bentuk dari oraktik sosial. Analisis wacana kritis memiliki berbagai teori salah satunya ialah analisis wacana kritis dengan model Norman Fairclough yang dianggap lengkap yang memabagi teks menjadi tiga dimensi, dimensi ini meliputi: (a) Dimensi tekstual (Mikrostruktural) yang meliputi representasi, relasi dan identitas, (b) Dimensi praktik produksi teks (Meso-Struktural) yang meliputi, produksi teks, penyebaran teks dan konsumsi teks, (c) dimensi praktik sosial budaya (Makrostruktural) yang meliputi institusional, situasional dan sosial. Dari hasil analisis yang dilakukan ditemukan ketiga dimensi ini dalam berita yang dijadikan sebagai objek kajian. Dengan demikian berita tersebut terbilang baik dan sesuai.